Nanopartículas multifuncionais de fluoreto de lantânio dopadas com Nd3+ como agentes de contrastes e terapêuticos - Silva, Uéslen Rocha (2014)
In this work, we investigated the possible applications of Nd3+ ions doped lanthanium trifluoride (LaF3) nanocrystals as infrared constrast agents in the first and second biological windows of the electromagnetic spectrum, which extend from 700 to 1400 nm. For this, we use the three emissions of Nd3+ ions centered around 900, 1060, and 1330 nm, corresponding to transitions generated from the metastable state 4F3/2. In comparison with other fluorescent nanoparticles (NPs) used as biolables agents, such as semiconductor quantum dots and multiphotonic luminescent NPs, the Nd3+ doped LaF3 NPs present several advantages such as high fluorescence quantum efficiency and high chemical and spectral stabilities. We have demonstrated that, with the emission around 1060 nm is possible to obtain high brightness images of cancer cells and high penetration images of animal models (mices). Additionally, we have demonstrated that the emission around 900 nm has an appreciable thermal sensitivity that allows the use of such NPs as optical nanothermometers. As the Nd3+ concentration is increased to values around 25 mol%, this thermal sensitivity comes with a high conversion efficiency of light-to-heat, so that the NPs work as multifunctional agents capable of generating heat and measuring, simultaneously, induced local temperature. This has allowed the development of real time controlled thermal therapies of cancerous tumors in animal models (mices).